(untitled) (Politeja, 2023)
This article examines the leadership of Ukrainian President Volodymyr Zelensky. It applies three features of Bernard M. Bass’s concept of idealized influence of transformational leadership: high ethical conduct, collective sense of mission, and perception of confidence. The author considers the results of the analysis and explains why these findings are important. While the study covers the political-scientific analysis of President Zelensky’s leadership, its particular novelty lies in the use of Bass’s theory of transformational leadership, formulated on the basis of management and organization science.